Urodynamic assessment of urinary incontinence - Housley, Sarah L. (Medknow Publications, 2010)
CONTEXT: Urodynamic evaluation in the assessment of women complaining of urinary incontinence remains controversial with recent UK National Institute of Health and Clinical Excellence guidance maintaining that it is unnecessary prior to surgery for women with a primarily stress leakage. Other experts contend it should be part of routine preoperative assessment since it establishes a diagnosis, allows more careful patient counseling and predicts surgical outcome. OBJECTIVES: To summarize current literature to define the evidence level on which these conflicting opinions are based. MATERIALS AND METHODS: A systematic literature search was performed and retrieved publications summarized in a narrative evidence review using both original papers and previous reviews. RESULTS: Five hundred and one primary research papers and 65 previous reviews were retrieved. The findings were summarized in a narrative comprising overview, description of methods of bladder and urethral pressure measurement, and a summary of the literature concerning four key questions. CONCLUSION: The level of evidence was low regarding answering each of the questions posed, preventing firm conclusions. Urodynamic findings do correlate with relevant symptoms and, to some extent, with symptom severity, giving reasonable diagnostic accuracy. There is no reliable evidence that preoperative urodynamic diagnosis improves outcome from surgery for stress incontinence although it is likely to facilitate preoperative discussion. Tests to differentiate sphincter deficiency and urethral hypermobility are not currently recommended due to poor validity and reproducibility. This along with the current use of mid-urethral tapes as the universal primary surgical procedure means differentiation is not a necessity. Preoperative diagnosis of detrusor overactivity does not appear to worsen surgical outcome in women with a primary symptom of stress leakage. Large, well-designed prospective studies are now underway to provide a definitive answer to these questions.